DISTRIBUTION OF EXTREMOPHILIC BACILLI IN WATERS OF LAKE SEVAN BASIN (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
The distribution of mesophilic and extremophilic bacilli in Lake Sevan water and silt, as well as in artesian and subsoil waters from boreholes at the Dzknaget River estuary was studied. New cultures of extremophilic bacilli, including thermophilic, alcalophilic, halophilic and psichrophilic forms, were isolated.
Keywords: mesophilic and extremophilic bacilli; Lake Sevan water; Dzknaget River